Enhancing Studentsâ Competency and Learning Experience in Structural Engineering through Collaborative Building Design Practices - Rahmawati, Y. (MDPI, 2022)
The field of the built environment is evolving, whereby the involvement of a multi-disciplinary team in the project becomes necessary. Complexities of issues keep challenging the industry of Architecture, Engineering and Construction (AEC) and address the importance of skills in collaborative work to deliver a great building design. A building that is not only aesthetic but also durable, sturdy, sustainable, and has positive influences on the surroundings. That said, collaboration skills become essential for students in the field of AEC. Concerning this current need in the industry, it becomes necessary for the educators as well as the undergraduate programs, especially in the field of AEC, to facilitate the students with exposure to a multi-disciplinary environment, to enhance the readiness of their graduates in the industry. The current pandemic makes the efforts harder. This study presents a case study-based research on enhancing the competency and learning experience of students through an international and multi-disciplinary collaborative environment in the form of joint studio assignments involving students of architecture and civil engineering. Both qualitative and quantitative approaches through triangulation methodology were used in the study. Results showed that students could enhance their knowledge as well as their skill to collaborate, especially in the design process. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.